2000
DOI: 10.1038/sj.bjp.0703727
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Ca2+ regulatory sites of skeletal troponin C in modulating muscle fibre reactivity to the Ca2+ sensitizer bepridil

Abstract: 1 The Ca 2+ -sensor protein troponin C (TnC) exerts a key role in the regulation of muscle contraction, and constitutes a target for Ca 2+ sensitizer compounds, such as bepridil, known to increase its apparent Ca 2+ a nity. Moreover, bepridil has been reported to exert a di erential e ect in slow and fast skeletal muscle ®bres, which express the slow/cardiac and fast TnC isoform, respectively. 2 The role of the TnC isoform in establishing the di erential e ect of bepridil was assessed in slow soleus and fast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The level of endogenous RLC phosphorylation was shown to be a crucial determinant of the Ca 2ϩ sensitivity of force development. Moreover, increased phosphorylation of myosin light chains was associated with slow-to-fast transition in rat atrophied soleus (46). These data showed that posttranslational modifications can play an important role even if a large part of the protein is not constitutively modified.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The level of endogenous RLC phosphorylation was shown to be a crucial determinant of the Ca 2ϩ sensitivity of force development. Moreover, increased phosphorylation of myosin light chains was associated with slow-to-fast transition in rat atrophied soleus (46). These data showed that posttranslational modifications can play an important role even if a large part of the protein is not constitutively modified.…”
Section: Discussionmentioning
confidence: 67%
“…Some of these proteins, MLC2 and MLC1, corresponded also to phosphoproteins. Indeed, 30% of MLC2 slow and fast isoforms are phosphorylated in soleus and EDL, respectively (46). The level of endogenous RLC phosphorylation was shown to be a crucial determinant of the Ca 2ϩ sensitivity of force development.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is reminiscent of our previous work on EMD 57033 and cTnI 128 -147 [147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163] . This is somewhat surprising, because bepridil has been shown to increase both the activity of actomyosin ATPase and force generation in vitro (19,20), and this increase was observed in both slow/cardiac and fast skeletal muscle fibers, with the effect being greater in slow/cardiac fibers (37). However, this is in agreement with a recent study (21) that shows an apparent weaker binding of bepridil to the cTnC regulatory domain in the cTnC⅐cTnI complex (ϳ140 M) than to the isolated cTnC (ϳ10 M), and bepridil is also shown to inhibit calmodulin from binding to its target proteins (38 Table I.…”
Section: Structural Calculationsmentioning
confidence: 79%
“…The tension (T)-pCa curves were obtained as previously described (16). The steepness of the T-pCa curve was determined by the Hill coefficients n H, either n1 or n2, according to the following equation (4)…”
Section: Calcium Activation Characteristics Of Single Skinned Skeletamentioning
confidence: 99%
“…All solutions were described previously (16), and pCa values were calculated with the Fabiato (8) computer program. The calculation was performed with the stability constants listed for Ca 2ϩ (24).…”
Section: Calcium Activation Characteristics Of Single Skinned Skeletamentioning
confidence: 99%